Mathematics - Johnson, Trevor; Neill, Hugh. (Lincolnwood, Ill. : Contemporary Books, 2001)
A step-by-step introduction to the basic concepts and techniques of mathematics that includes practice exercises and examples.
Includes index.
Spine title: Teach yourself mathematics.
Adult
Keywords: Mathematics; Mathematics